2002
DOI: 10.1159/000065216
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin for the Prevention of Deep Venous Thrombosis: A Suitable Monitoring in Elderly Patients?

Abstract: Monitoring of anti-Xa activity (aXa) levels is not routinely required in patients receiving enoxaparine at prophylactic dosages, since aXa is supposed to stay below the manufacturer’s recommended range in patients treated for venous thrombosis (0.5–1 IU/ml). In order to aXa in elderly subjects receiving prophylactic enoxaparin, 68 consecutive patients (mean age 82.5 ± 10.7 years) hospitalized in a medical department receiving 4,000 IU enoxaparin daily subcutaneously for the prevention of venous thromboembolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The relationship between age‐associated bleeding and anticoagulation with LMWH/heparinoids has not been directly examined in clinical trials. Prophylactic administration of enoxaparin (4000 IU, subcutaneous, once daily) for the prevention of VTE in elderly hospitalized medical patients (82.5 ± 10.7 years) produced anti‐FXa levels above the manufacturer's recommended lower limit in more than 50% of the study population; anti‐FXa levels in this study were positively correlated with age (trend) but not with creatinine clearance, and were negatively correlated with weight [49]. Repeated administration of nadroparin (180 anti‐FXa IU kg −1 , once daily, 6–10 days) led to significant accumulation of anti‐FXa activity in healthy elderly volunteers (65 ± 3 years) and in elderly patients with DVT (65 ± 11 years) but not in a control group of young healthy volunteers (25 ± 4 years) [50].…”
Section: Age‐associated Bleeding Riskmentioning
confidence: 97%
“…The relationship between age‐associated bleeding and anticoagulation with LMWH/heparinoids has not been directly examined in clinical trials. Prophylactic administration of enoxaparin (4000 IU, subcutaneous, once daily) for the prevention of VTE in elderly hospitalized medical patients (82.5 ± 10.7 years) produced anti‐FXa levels above the manufacturer's recommended lower limit in more than 50% of the study population; anti‐FXa levels in this study were positively correlated with age (trend) but not with creatinine clearance, and were negatively correlated with weight [49]. Repeated administration of nadroparin (180 anti‐FXa IU kg −1 , once daily, 6–10 days) led to significant accumulation of anti‐FXa activity in healthy elderly volunteers (65 ± 3 years) and in elderly patients with DVT (65 ± 11 years) but not in a control group of young healthy volunteers (25 ± 4 years) [50].…”
Section: Age‐associated Bleeding Riskmentioning
confidence: 97%
“…A study by Mahe et al [67] evaluated anti-Xa levels of 68 consecutive hospitalized elderly patients (mean age of 82 years) receiving enoxaparin, 40 mg SC, daily. They found that even by day 2, over one-half of the patients had an anti-Xa level of greater than 0.5 IU/mL, which is considered an optimal treatment level.…”
Section: Elderly Patientsmentioning
confidence: 99%
“…Age-related reductions in creatinine clearance, low body weight, risk of falls, and an increased risk of intracranial bleeding are concerns in employing standard dose prophylaxis in the elderly. A study by Mahe et al [67] evaluated anti-Xa levels of 68 consecutive hospitalized elderly patients (mean age of 82 years) receiving enoxaparin, 40 mg SC, daily. They found that even by day 2, over one-half of the patients had an anti-Xa level of greater than 0.5 IU/mL, which is considered an optimal treatment level.…”
Section: Elderly Patientsmentioning
confidence: 99%
“…Moreover, they are not significantly influenced by the presence of therapeutic concentrations of LMWHs or the indirect FXa inhibitors such as fondaparinux [ 3 ]. Measuring of anti-Xa activity in plasma from patients treated with LMWHs has a limited predictive value for the clinical outcome [ 4 ] and in some patients' populations (i.e elderly or obese patients) the anti-Xa levels in plasma are poorly correlated with the administered dose of LMWH [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%